Comparison of adsorption of mercaptopropyltrimethoxysilane on amphiphilic TiO 2 and hydroxylated SiO 2 (2010)
Alkylsilane 3-mercaptopropyltrimethoxysilane (3MPT) monolayers with a functional end group -SH were used to immobilize Ag colloidal nanoparticles on photoinduced amphiphilic TiO 2 and hydroxylated SiO 2 surfaces. The differences in the adsorption of 3MPT and the immobilization of Ag colloids on both surfaces were studied. Under identical experimental conditions, 3MPT islands were formed on UV-exposed TiO 2 surfaces compared to continuous and flat monolayers formed on SiO 2. The significant structural differences found for monolayers of 3MPT on TiO 2 could be explained in terms of the different densities of hydroxyl groups and the microstructure of hydrophilic domains induced by UV irradiation. The surface properties were characterized using contact angle measurements and XPS. XPS showed an increase in the hydroxyl group's density and a decrease in the number of adsorbed hydrocarbon films on the TiO 2 surface as a function of the UV irradiation time. The density of the adsorbed 3MPT on TiO 2 surfaces as a function of theUVirradiation time was quantitatively related to the cosine of the water contact angles. Such a 3MPT distribution influenced the subsequent adsorption of Ag colloids and resulted in more isolated nanoparticles on the modified TiO 2 with a narrower size distribution. © 2010 American Chemical Society.